Detoxification in Abdominal Sepsis - A. F. Potapov; T. M. Tyaptirgyanova; A. N. Kirillin (Общая реаниматология, 2005)
Objective. To comparatively analyze the efficiency of methods for extracorporeal detoxification (ED) of the body in abdominal sepsis (AS) and to choose the optimum detoxifying methods in relation to the level of endotoxicosis.Material and methods. 56 patients (41 males and 15 females; mean age 39.4±12.2 years) with surgical abdominal infection of various genesis, complicated by the development of sepsis whose treatment included ED methods, were examined. The level of intoxication and the efficiency of detoxification were evaluated by general clinical and biochemical blood parameters, the leukocytic intoxication index, the levels of low and medium molecular-weight substances in the body’s media. Hemosorption, plasmapheresis, hemodialysis, hemodiafiltration, and hemofiltration were used for detoxification.Results. Surgical abdominal infection is accompanied by endotoxemia that has no clear nosological specificity, but it depends on the pattern of a clinical course of the disease and is most pronounced in the septic syndrome. In AS, 80.4% of the patients are observed to have an irreversible decompensation phase and a terminal degree of endotoxicosis, which require detoxification. The use of different ED methods according to the level of intoxication may reduce the level of endotoxicosis and yield a persistent beneficial effect in 85.2% of cases of its application. Conclusion. Filtration and dialysis techniques (hemodialysis, hemofiltration, and hemodiafiltration) are the methods of choice in AS. Hemosorption and plasmapheresis may be recommended for use at the early stages of endotoxicosis development and in preserved renal excretory function.